Analysis of Third Grade Elementary School Students’ Numeracy Literacy Skills in Solving Contextual Problems with the Help of The PBL Model - Laura, Westi Devia; Wahyudin (International Conference on Elementary Education, 2025)
Initial observations indicate that elementary school students' numeracy literacy is still low, especially in connecting mathematical concepts to real-world contexts, so that the learning process has not been able to optimally develop numeracy skills. Based on these issues, this study aims to analyze students' numeracy literacy abilities in solving contextual problems with the help of the Problem-Based Learning (PBL) model. This study uses a quantitative approach with a pre-experimental design of one group pre-test and post-test. The results show a significant increase in numeracy literacy scores after the implementation of the PBL model, with a pretest average score of 60.03 (SD = 9.642) and a posttest average score of 78.14 (SD = 7.678), as well as an average difference of 18.114. A correlation value of 0.813 (p < 0.001) and a t-value of -19.089 (p < 0.001) indicate a strong positive effect, with a very large effect size (Cohen's d = -3.227). These findings prove that problem-based learning is effective in improving numeracy literacy by strengthening elementary school students' critical thinking and contextual problem-solving skills.